Facilitating meaningfulness in the workplace: a field intervention study. Issue 14 (6th August 2021) - Fletcher, Luke; Schofield, Keith
Abstract: This article presents the findings of a field intervention study that sought to address two objectives: (a) what are the psychological effects of a meaningfulness intervention? and (b) what key issues should be considered when developing meaningfulness interventions? Eighty employees from three different organizations based in the UK were allocated to either the intervention condition or a wait-list control group. Compared against the wait-list control group, the meaningfulness intervention facilitated meaningfulness in / at work, job/organization engagement, and personal initiative. Finally, focus group interviews revealed a number of micro (e.g., sustaining motivation), meso (e.g., role of line managers) and macro (e.g., socio-political events) level issues that should be considered when planning and implementing meaningfulness interventions. Overall this study makes use of field intervention research in order to develop the rationale for incorporating meaningfulness theories and concepts within HRM practice, particularly in better aligning personal development, team-based learning and performance management activities.